2008
DOI: 10.1111/j.1540-8191.2008.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Replacements in Redo Patients with Previous Mitral Valve Procedures: Mid-Term Results and Risk Factors for Survival

Abstract: Redo mitral valve surgery with mechanical prosthesis offers encouraging short- and mid-term survival. NYHA functional class IV, low left ventricular ejection fraction, and increased left ventricular diameters were especially associated with increased short- and mid-term mortality. Earlier surgical management before the development of severe heart failure and myocardial dysfunction would improve the results of redo mitral valve surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 20 publications
6
33
0
Order By: Relevance
“…Another factor to consider is that some studies had also included patients who previously underwent MV procedures other than replacement (e.g. MV repair and mitral valvuloplasty) [16,19]. In our study, hospitaly mortality was (11.5%) which is concordant with the recent literature [3,5,12], despite the fact that 66.7% of our patients had concomitant procedures.…”
Section: Commentsupporting
confidence: 81%
See 3 more Smart Citations
“…Another factor to consider is that some studies had also included patients who previously underwent MV procedures other than replacement (e.g. MV repair and mitral valvuloplasty) [16,19]. In our study, hospitaly mortality was (11.5%) which is concordant with the recent literature [3,5,12], despite the fact that 66.7% of our patients had concomitant procedures.…”
Section: Commentsupporting
confidence: 81%
“…In this study, we had not found any correlation between pre-operative and operative variables and prediction of prolonged hospital stay. It is also In some studies, early mortality had been associated with older age [3,5,18], female gender [16], advanced NYHA class [16,19], low left ventricular ejection fraction (<35), increased left ventricular enddiastolic diameter (>50 mm), pulmonary oedema, urgent operations [3,16,12], concomitant procedures [5,19] and previous myocardial infarction [12]. we found that preoperative impairment of the LVEF remains the most consistent risk factor for early and overall mortality following redo-MVR.…”
Section: Commentmentioning
confidence: 92%
See 2 more Smart Citations
“…Increased rates of valve replacement in females are associated with perioperative left ventricular dysfunction, arrhythmias, and bleeding [57]. Furthermore, the presence of postoperative mitral regurgitation in the setting of ischemic heart disease is more common in women; this increases the risk for postoperative complications and need for readmission, as well as reducing 5-year survival [58].…”
Section: Cabg/valve Surgerymentioning
confidence: 99%